Promoting community health and climate justice co-benefits: insights from a rural and remote island climate planning process - Kennedy, Angel M.; Tsakonas, Kiera; Berman-Hatch, Forrest; Conradi, Sophia; Thaysen, Max; Gillespie, Manda Aufochs; Gislason, Maya K. (Frontiers in Public Health, 2024)
Climate change is an environmental crisis, a health crisis, a socio-political and an economic crisis that illuminates the ways in which our human-environment relationships are arriving at crucial tipping points. Through these relational axes, social structures, and institutional practices, patterns of inequity are produced, wherein climate change disproportionately impacts several priority populations, including rural and remote communities. To make evidence-based change, it is important that engagements with climate change are informed by data that convey the nuance of various living realities and forms of knowledge; decisions are rooted in the social, structural, and ecological determinants of health; and an intersectional lens informs the research to action cycle. Our team applied theory- and equity-driven conceptualizations of data to our work with the community on Cortes Island—a remote island in the northern end of the Salish Sea in British Columbia, Canada—to aid their climate change adaptation and mitigation planning. This work was completed in five iterative stages which were informed by community-identified needs and preferences, including: An environmental scan, informal scoping interviews, attending a community forum, a scoping review, and co-development of questions for a community survey to guide the development of the Island’s climate change adaptation and mitigation plan. Through this community-led collaboration we learned about the importance of ground truthing data inaccuracies and quantitative data gaps through community consultation; shifting planning focus from deficit to strengths- and asset-based engagement; responding to the needs of the community when working collaboratively across academic and community contexts; and, foregrounding the importance of, and relationship to, place when doing community engagement work. This suite of practices illuminates the integrative solution-oriented thinking needed to address complex and intersecting issues of climate change and community health.